Colour-temperature correspondences: when reactions to thermal stimuli are influenced by colour - Ho, H; Van Doorn, G; Kawabe, T; Watanabe, J; Spence, C (Public Library of Science, 2014)
In our daily lives, information concerning temperature is often provided by means of colour cues, with red typically being associated with warm/hot, and blue with cold. While such correspondences have been known about for many years, they have primarily been studied using subjective report measures. Here we examined this correspondence using two more objective response measures. First, we used the Implicit Association Test (IAT), a test designed to assess the strength of automatic associations between different concepts in a given individual. Second, we used a priming task that involved speeded target discrimination in order to assess whether priming colour or thermal information could invoke the crossmodal association. The results of the IAT confirmed that the association exists at the level of response selection, thus indicating that a participant's responses to colour or thermal stimuli are influenced by the colour-temperature correspondence. The results of the priming experiment revealed that priming a colour affected thermal discrimination reaction times (RTs), but thermal cues did not influence colour discrimination responses. These results may therefore provide important clues as to the level of processing at which such colour-temperature correspondences are represented.